Analisis Konsep Interpretasi Nilai Karakter pada Film The Asadas! (Asadake!) terhadap Pertumbuhan Pengembangan Teknologi Informasi dan Manajemen Data - Pramudibyanto, Hascaryo (KIRYOKU, 2023)
This article aims to analyze the content of the film "The Asadas! (Asadake!)" in relation to the aspect of character value interpretation relevant to the development of information technology and data management. The film "The Asadas! (Asadake!)" exhibits strong strengths in terms of its storytelling structure, which contains a combination of comedy, drama, and science fiction elements in an environment facing drastic changes due to advances in information technology and data management. Using a media content analysis approach, an analysis of scenes, dialogues, and characters relevant to the development of information technology and data management was conducted by 24 viewers over 2 days, with a film duration of 92 minutes. Viewers and interpreters of the film "The Asadas! (Asadake!)" stated that the film focuses on human relationships, life experiences, and human character in facing unique situations that illustrate the principles of information system science regarding the form of technological and informational adaptation qualifications. There were positive values acquired by the viewers even though the characters had age differences, but each was able to recognize their needs. This demonstrates collaboration and positive synergy to reach a conflict resolution that can become a habit. Therefore, there is a need for other film products, especially in Indonesia, that can utilize the use of information data as a basis for decision-making in changing the positive attitudes of others.